1996
DOI: 10.1037/0096-1523.22.1.42
|View full text |Cite
|
Sign up to set email alerts
|

Spatial patterns in the control of human arm movement.

Abstract: Generalized Procrustes analysis was used to investigate the spatial paths of pointing movements. In Experiment 1, 3 participants produced similar spatial paths of the hand when repeating a pointing movement many times, despite variability in the position and orientation of the movements. The average spatial path indicates a fundamental spatial pattern of the motor system, or motor primitive. This pattern varied across the workspace. Anterioposterior movements were straight, but repeated movements had variable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
53
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 29 publications
(67 reference statements)
7
53
1
Order By: Relevance
“…First, when targets are specified for the hand, that is, in the absence of the kinematic transformation of the tool, hand paths are almost straight even in the absence of continuous visual feedback. Without the dynamic transformation of the tool, there is a slight concave curvature, consistent with findings of Haggard and Richardson (1996), Wolpert et al (1994), and Van Thiel et al (1998). With the dynamic transformation we found a slight convex curvature.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…First, when targets are specified for the hand, that is, in the absence of the kinematic transformation of the tool, hand paths are almost straight even in the absence of continuous visual feedback. Without the dynamic transformation of the tool, there is a slight concave curvature, consistent with findings of Haggard and Richardson (1996), Wolpert et al (1994), and Van Thiel et al (1998). With the dynamic transformation we found a slight convex curvature.…”
Section: Discussionsupporting
confidence: 78%
“…Consistent with previous observations, we expected almost straight movement paths or a slight concave curvature (Haggard and Richardson 1996;Wolpert et al 1994;Van Thiel et al 1998) and only little or no influence of the absence versus presence of the dynamic transformation . In the presence of the kinematic transformation targets were defined for the tip of the lever.…”
Section: Methodssupporting
confidence: 78%
See 1 more Smart Citation
“…10, 3 right panels) as well as Coriolis (thin solid line), centripetal (dashed line), and inertial interaction (dashed-dotted line) torque components of fast reaching movements to each target performed by 1 subject in the light condition. the computational complexity of executing the path (Haggard and Richardson 1996;Haggard et al 1995). In addition, biomechanical constraints (e.g., the hand coming in too close proximity to the trunk) may also partly explain the outward curvature of finger trajectories involving significant trunk contribution.…”
Section: Coriolis Force Magnitude and Reaching Errorsmentioning
confidence: 99%
“…Morasso (1981) observed that point-to-point aiming movements indeed tend to be performed along straight paths. Minimum torquechange trajectories, however, show systematic curvature variations, depending on where a particular aiming movement is performed in workspace, as experimentally con®rmed by Atkeson and Hollerbach (1985), Uno et al (1989), Haggard and Richardson (1996), Van Thiel et al (1998), and Boessenkool et al (1998). Although it has been demonstrated that curved movements can be accounted for by both models by presuming via points, i.e., intermediate locations through which the hand must move on its way to the prede®ned end location, it is not clear how these models account for systematic variations in curvature of the trajectory due to self-or externallyimposed end-point constraints such as the angle and speed with which a target area is approached.…”
Section: Introductionmentioning
confidence: 99%